2013
DOI: 10.1002/bit.24923
|View full text |Cite
|
Sign up to set email alerts
|

Investigating contactless high frequency ultrasound microbeam stimulation for determination of invasion potential of breast cancer cells

Abstract: In this article, we investigate the application of contactless high frequency ultrasound microbeam stimulation (HFUMS) for determining the invasion potential of breast cancer cells. In breast cancer patients, the finding of tumor metastasis significantly worsens the clinical prognosis. Thus, early determination of the potential of a tumor for invasion and metastasis would significantly impact decisions about aggressiveness of cancer treatment. Recent work suggests that invasive breast cancer cells (MDA-MB-231)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 29 publications
3
44
0
Order By: Relevance
“…Furthermore, the low-frequency ultrasound affected nuclear processes of the cells including the expression of early response gens c-Fos, c-Jun, and c-Myc while the magnitude of effect depended on the ultrasound frequency (Louw et al 2013). In contrast, we recently demonstrated that high-frequency ultrasound microbeam was better suited for more localized single-cell stimulation (Hwang et al 2012; Hwang et al 2013) than the low-frequency ultrasound. Particularly, high-frequency ultrasound microbeam stimulation (HFUMS) allowed identifying functional characteristics of cells and also discriminating cell types (Hwang et al 2012; Hwang et al 2013).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, the low-frequency ultrasound affected nuclear processes of the cells including the expression of early response gens c-Fos, c-Jun, and c-Myc while the magnitude of effect depended on the ultrasound frequency (Louw et al 2013). In contrast, we recently demonstrated that high-frequency ultrasound microbeam was better suited for more localized single-cell stimulation (Hwang et al 2012; Hwang et al 2013) than the low-frequency ultrasound. Particularly, high-frequency ultrasound microbeam stimulation (HFUMS) allowed identifying functional characteristics of cells and also discriminating cell types (Hwang et al 2012; Hwang et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, we recently demonstrated that high-frequency ultrasound microbeam was better suited for more localized single-cell stimulation (Hwang et al 2012; Hwang et al 2013) than the low-frequency ultrasound. Particularly, high-frequency ultrasound microbeam stimulation (HFUMS) allowed identifying functional characteristics of cells and also discriminating cell types (Hwang et al 2012; Hwang et al 2013). In these studies, it was found that HFUMS resulted in more reduction of mitochondrial membrane potentials in breast cancer cells than in normal cells, thus showing its capability to discriminate between the functional characteristics of the cells (Hwang et al 2012; Hwang et al 2013).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In those studies, the calcium response of the cells to high-frequency ultrasonic stimulation was dependent on the applied acoustic pressure. Therefore, it was shown that both umbilical vein endothelial cells and highly-invasive cancer responded less actively at the lower acoustic excitation (input voltage = ~8 V pp and ~9.5 V pp ) [24]. Similarly, the calcium response of SKBR-3 cells is here little affected by non-FNT-coated microbead attachment under acoustic excitation at 6.3 V pp (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3, it is shown that attachment of the acoustically trapped FNT-coated microbead to the SKBR-3 cells clearly induces significant intracellular calcium elevations compared to attachment of the trapped non-FNT microbead to the cells. Our previous studies have shown that 200 MHz ultrasound microbeams themselves were able to promote intracellular calcium elevations in highly-invasive breast cancer cells (MDA-MB-231), but not in weakly-invasive breast cancer cells such as SKBR-3 cells [24]. In addition, such a high-frequency ultrasonic stimulation resulted in considerable cytoplasmic calcium elevations in human umbilical vein endothelial cells [25].…”
Section: Discussionmentioning
confidence: 99%